The impact of multimodality integrated positron emission tomography-computed tomography on improving the staging and management of head and neck malignancy: a cross- sectional study - Subha, Sethu Thakachy; Nordin, Abdul Jalil (Paulista Medical Association, 2022)
Background: Clinical assessment of head and neck cancers is highly challenging owing to the complexity of regional anatomy and wide range of lesions. The diagnostic evaluation includes detailed physical examination, biopsy and imaging modalities for disease extent and staging. Appropriate imaging is done to enable determination of precise tumor extent and involvement of lymph nodes, and detection of distant metastases and second primary tumors. Objective: To evaluate the initial staging discrepancy between conventional contrasted computed tomography (CT) and 18F-fluorodeoxy-D-glucose positron emission tomography/computed tomography (18F-FDG PET/CT) and its impact on management plans for head and neck malignancies. Design and setting: Prospective cross-sectional study in two tertiary-level hospitals. Methods: This study included 30 patients with primary head and neck malignant tumors who underwent contrasted computed tomography and whole-body 18F-FDG PET/CT assessments. The staging and treatment plans were compared with the incremental information obtained after 18F-FDG PET/CT. Results: 18F-FDG PET/CT was found to raise the stage in 33.3% of the cases and the treatment intent was altered in 43.3% of them, while there was no management change in the remaining 56.7%. 18F-FDG PET/CT had higher sensitivity (96% versus 89.2%) and accuracy (93% versus 86.7%) than conventional contrast-enhanced computed tomography. Conclusion: Our study demonstrated that 18F-FDG PET/CT had higher sensitivity and accuracy for detecting head and neck malignancy, in comparison with conventional contrast-enhanced computed tomography. 18F-FDG PET/CT improved the initial staging and substantially impacted the management strategy for head and neck malignancies.